The silicon solution [silicon photonics]. - Panicia, M.
As newer, faster microprocessors roll out, the copper connections that feed those processors within computers and servers will prove inadequate to handle huge amounts of data. To address this concern, this paper proposes the replacement of the copper with optical fiber and the electrons with photons. Called silicon photonics, this technology will allow manufacturers to build optical components using the same semiconductor equipment and methods they use now for ordinary integrated circuits. This would dramatically lower the cost of photonics while significantly improving performance.
Keywords: Copper connections; Electrons; Integrated circuits; Optical communications; Optical components; Optical fiber; Optical transceiver; Photons; Printed circuit board; Semiconductor equipments; Silicon chip; Silicon photonics